2018
DOI: 10.1016/j.neucom.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of deep neural networks for traffic sign detection systems

Abstract: Traffic sign detection systems constitute a key component in trending real-world applications, such as autonomous driving, and driver safety and assistance. This paper analyses the stateof-the-art of several object-detection systems (Faster R-CNN, R-FCN, SSD, and YOLO V2) combined with various feature extractors (Resnet V1 50, Resnet V1 101, Inception V2, Inception Resnet V2, Mobilenet V1, and Darknet-19) previously developed by their corresponding authors. We aim to explore the properties of these object-dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(97 citation statements)
references
References 33 publications
0
94
0
3
Order By: Relevance
“…The traffic sign detection and recognition problem has been investigated by the research community for a while. Researchers have been proposing all types of solutions such as the ones using hand-crafted features in model-based solutions [9], leveraging simple features in learning-based approaches [10], and, the more recent and state-of-the-art, using deep learning based methods [6], [11] that is the focus of this work. A detailed and complete review of these methods can be found in [12].…”
Section: Introductionmentioning
confidence: 99%
“…The traffic sign detection and recognition problem has been investigated by the research community for a while. Researchers have been proposing all types of solutions such as the ones using hand-crafted features in model-based solutions [9], leveraging simple features in learning-based approaches [10], and, the more recent and state-of-the-art, using deep learning based methods [6], [11] that is the focus of this work. A detailed and complete review of these methods can be found in [12].…”
Section: Introductionmentioning
confidence: 99%
“…8. Faster R-CNN Inception Resnet V2 model architecture [53] for iris certification. The CRR of the three iris libraries compared to the existing algorithms are shown in Table 9.…”
Section: Existing Methods Comparison Experimentsmentioning
confidence: 99%
“…By these methods a feature vector is extracted from image with lower computational cost than from 3-D point cloud. Then, the class label of the feature vector is obtained using a classifier such as Support Vector Machine (SVM) or with Deep Learning-based (DL) methods [42][43][44]. Among the latter, Convolutional Neural Networks (CNN) have been widely adopted, given their high performance in both TSD and TSR in images [45][46][47][48] and in point clouds [49].…”
Section: Related Workmentioning
confidence: 99%